2022
DOI: 10.3389/fcell.2022.908790
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage, a potential targeted therapeutic immune cell for cardiomyopathy

Abstract: Cardiomyopathy is a major cause of heart failure, leading to systolic and diastolic dysfunction and promoting adverse cardiac remodeling. Macrophages, as key immune cells of the heart, play a crucial role in inflammation and fibrosis. Moreover, exogenous and cardiac resident macrophages are functionally and phenotypically different during cardiac injury. Although experimental evidence has shown that macrophage-targeted therapy is promising in cardiomyopathy, clinical translation remains challenging. In this ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 89 publications
0
8
0
Order By: Relevance
“…DCM is associated with an imbalanced M1-to-M2-macrophage ratio [15]. Multiple studies have reported a predominantly M1 phenotype in DCM, contributing to cardiac fibrosis and impaired cardiac function [15,41].…”
Section: Macrophages and Inflammation In Dcmmentioning
confidence: 99%
See 3 more Smart Citations
“…DCM is associated with an imbalanced M1-to-M2-macrophage ratio [15]. Multiple studies have reported a predominantly M1 phenotype in DCM, contributing to cardiac fibrosis and impaired cardiac function [15,41].…”
Section: Macrophages and Inflammation In Dcmmentioning
confidence: 99%
“…DCM is associated with an imbalanced M1-to-M2-macrophage ratio [15]. Multiple studies have reported a predominantly M1 phenotype in DCM, contributing to cardiac fibrosis and impaired cardiac function [15,41]. M1 macrophage-activated pro-inflammatory cytokines, such as tumor necrosis factor-alpha (TNF-α), interleukin-1 beta (IL-1β), and IL-6, promote inflammation, oxidative stress, and cardiomyocyte apoptosis.…”
Section: Macrophages and Inflammation In Dcmmentioning
confidence: 99%
See 2 more Smart Citations
“…M1 macrophages mediate the removal of dead cells and ECM debris. Cytokines secreted from M1 macrophages gradually increase the infarct size ( Duncan et al, 2020 ; Chen et al, 2022 ). Contrastingly, M2 macrophages are involved in drafting fibroblasts to the injury site and secreting pro-fibrotic mediators such as IL-10, TGF-β, and platelet-derived growth factor (PDGF) ( Frangogiannis, 2019 ; Viola et al, 2019 ; Kim et al, 2021 ).…”
Section: Major Contributors Of Cardiac Fibrosismentioning
confidence: 99%